Loop and void damage during heavy ion irradiation on nanocrystalline and coarse grained tungsten: Microstructure, effect of dpa rate, temperature, and grain size. (1st May 2018) - El-Atwani, O.; Esquivel, E.; Efe, M.; Aydogan, E.; Wang, Y.Q.; Martinez, E.; Maloy, S.A.
Abstract: Displacement damage, through heavy ion irradiation was studied on two tungsten grades (coarse grained tungsten (CGW) and nanocrystalline and ultrafine grained tungsten (NCW)) using different displacement per atom rates and different irradiation temperatures (RT and 1050 K). Percentage of <111> and <100> type loops at the irradiation conditions was determined. Irradiation damage in the microstructure was quantified using average loop areas and densities (method A) and loop areal fraction in the grain matrices under 2-beam diffraction conditions (method B). Average values of <111> and <100> loops were calculated from method A. Loop coalescence was shown to occur for CGW at 0.25 dpa. Using both methods of quantifying microstructural damage, no effect of dpa rate was observed and damage in CGW was shown to be the same at RT and 1050 K. Swelling from voids observed at 1050 K was quantified. The loop damage in NCW was compared to CGW at the same diffraction and imaging conditions. NCW was shown to possess enhanced irradiation resistance at RT regarding loop damage and higher swelling resistance at 1050 K compared to CGW. For irradiation at 1050 K, the NCW was shown to have similar defect densities to the CGW which is attributed to higher surface effects in the CGW, vacancy loop growth to voids and a better sink efficiency in the CGW deduced from the vacancy distribution profiles from Kinetic Monte Carlo simulations. Loop density and swelling was shown to have similar values in grains sizes that range from 80 to 600 nm. No loop or void denuded zones occurred at any of the irradiation conditions. This work has a collection of experiments and conclusions that are of vital importance to materials and nuclear energy communities. Graphical abstract: Image 1